Profiling Land Use Planning: Legislative Structures in Five European Nations - Dimitrios Koumoulidis; Ioannis Varvaris; Diofantos Hadjimitsis; Marzia Gabriele; Raffaella Brumana; Ioannis Gitas; Nikos Georgopoulos; Azadeh Abdollahnejad; Eleni Gkounti; Dimitris Stavrakoudis; Donatella Caniani; Andriy Dorosh; et al. (Land)
Land use transformation, the longest-standing human-driven environmental alteration, is a pressing and complex issue that significantly impacts European landscapes and contributes to global environmental change. The urgency to act is reinforced by the European Environment Agency (EEA), which identifies industrial, commercial, and residential development—particularly near major urban centers—as key contributors to land take. As the EU sets a vision for achieving zero net land take by 2050, assessing the readiness and coherence of national legislation becomes critical. This comprehensive study employs a comparative legal analysis across five European countries—Italy, Greece, Poland, France, and Ukraine—examining their laws, strategies, and commitments related to land degradation neutrality. Using a review of national legislation and policy documents, the research identifies systemic patterns, barriers, and opportunities within current legal frameworks. The present study aims to provide valuable insights for policymakers, planners, and academic institutions, fostering a comprehensive understanding of existing gaps, implementation, and inconsistencies in national land use legislation. Among the results, it has become evident that a typical “pathway” between the examined states in terms of the legislative framework on land use–land take is probably a utopia for the time being. The legislations in force, in several cases, are labyrinthine and multifaceted, highlighting the urgent and immediate need for simplification and standardization. The need for this action is further underscored by the fact that, in most cases, land use frameworks are characterized by complementary legislation and ongoing amendments. Ultimately, the research underscores the critical need for harmonized governance and transparent, enforceable policies, particularly in regions where deregulated land use planning persists. The diversity in legislative layers and the decentralized role of the authorities further compounds the complexity, reinforcing the importance of cross-country dialogue and EU-wide coordination in advancing sustainable land use development.